Linalool: a key contributor to the aroma nuances in hoppy beer, cocoa liquor, wines, and fermented tea beverage - Olusegun, Lasekan; Muniandy, Megala; Teoh, Li Shing; Mee, Gie Lin (Nova Science Publishers, 2017)
Linalool (3,7-dimethyl-1,6-octadien-3-ol) is an important monoterpene alcohol that contributes to the flowery and tea-like flavour of some liquid food products such as cocoa liquor, wines, juices, and fermented tea (black tea). In addition, linalool has been reported as the most aromatic flavour odorant of hop essential oils and by extension hoppy beer. However, the mechanism of linalool formation in most of these liquid food products remains a subject of interest. It has been assumed that terpene alcohols are probably produced from oxygenated isoprenoid hydrocarbons. In addition, linalool has been shown to occur in two forms: (1) free form in juices and (2) non-volatile precursor form. The non-volatile precursors, which are monoterpene disaccharide glycosides, have been subjected to enzymatic hydrolysis to yield linalool.